PERKIRAAN SELANG KEPERCAYAAN UNTUK NILAI RATA-RATA PADA DISTRIBUSI POISSON - Randy Toleka Ririhena; Nur Salam; Dewi Sri Susanti (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2016)
Confidence interval is an interval between two value, where we believe that the parameter value lay within those interval. To express it, approximate interval were conducted. If the parameter value is unknown, probability will be use rather than exact value. Approximation that conduct express probability that an interval contain parameter value that we estimate. One of parameter value to compute is mean. One of well-known distribution is Poisson ditribution. The purpose of this study is to find approximate interval for the mean of random variable with Poisson distribution. The result of research is confidence interval for poisson distribution by using pivotal quantity method. Based on pivotal quantity method, approximate interval for the mean of poisson distribution with the size of a large sample is???????? ???? ????????????− ????????????????/2 ???????????????? ???????? < ???????? < ???????????? + ????????????????/2 ???????????????? ???????? ???? = 1− ????????